2019
DOI: 10.18632/aging.102215
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of subclinical thyroid dysfunction in ischemic stroke patients treated with intravenous thrombolysis

Abstract: Data regarding the association between subclinical thyroid dysfunction and clinical outcomes in ischemic stroke patients with intravenous thrombolysis (IVT) are limited. We aimed to investigate the predictive value of subclinical thyroid dysfunction in END, functional outcome and mortality at 3 months among IVT patients. We prospectively recruited 563 IVT patients from 5 stroke centers in China. Thyroid function status was classified as subclinical hypothyroidism, subclinical hyperthyroidism (SHyper) and euthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…In addition, multiple logistic regression models showed that age, diastolic blood pressure, HT, OTT, and PAO were connected with post-thrombolysis ENI. Previous researches confirmed that age, elevated levels of baseline NIHSS, OTT, and FBG may be able to be the risk factors of neurological recovery [ 7 , 8 , 46 ]. Moreover, HT could serve as one reason for END [ 6 , 47 ], and PAO may lead to symptoms worsening and poor prognosis in AIS patients [ 48 ].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, multiple logistic regression models showed that age, diastolic blood pressure, HT, OTT, and PAO were connected with post-thrombolysis ENI. Previous researches confirmed that age, elevated levels of baseline NIHSS, OTT, and FBG may be able to be the risk factors of neurological recovery [ 7 , 8 , 46 ]. Moreover, HT could serve as one reason for END [ 6 , 47 ], and PAO may lead to symptoms worsening and poor prognosis in AIS patients [ 48 ].…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that rapid recovery, which is described as early neurological improvement (ENI), can be observed in a significant proportion of AIS patients within the first 24 h after intravenous thrombolysis [ 3 , 4 ]. However, there are still several patients whose symptoms would worsen and neurological deficits may aggravate within 24 h after intravenous thrombolysis, named as early neurological deterioration (END) [ 6 8 ]. Previous researches indicate that post-thrombolysis early neurological outcomes, including post-thrombolysis END as well as post-thrombolysis ENI, are relevant to the prognosis of patients treated with intravenous thrombolysis [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, diverse multivariate regression models showed that age, diabetes mellitus, previous antiplatelet, diastolic blood pressure, HT, OTT as well as PAO were connected with ENI. Previous researches con rmed that age, diabetes mellitus and elevated levels of baseline NIHSS, OTT as well as FBG may be able to be the risk factors of neurological recovery [7,8,49]. Moreover, HT could serve as one reason for END [6,50], and PAO may lead to symptoms worsening and poor prognosis in AIS patients [51].…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that rapid recovery, which is described as early neurological improvement (ENI), can be observed in a signi cant proportion of AIS patients within the rst 24 hours after intravenous thrombolysis [3,4]. However, there are still several patients whose symptoms would worsen and neurological de cits may aggravate within 24 hours after intravenous thrombolysis, named as early neurological deterioration (END) [6][7][8]. Previous researches indicate that post-thrombolysis early neurological outcomes, including post-thrombolysis END as well as post-thrombolysis ENI, are relevant to the prognosis of patients treated with intravenous thrombolysis [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…As NAFLD is considered the cause or the consequence of metabolic syndrome, which is reflected primarily by raised visceral adiposity that promotes insulin resistance (IR), glucose intolerance, and overall a lipotoxic status, it is possible that its metabolic substrates may share pathogenic factors with hypothyroidism [ 13 , 14 , 15 , 16 ]. More than that, below range serum concentration of thyroid hormones (THs) has been linked to the development of metabolic syndrome, obesity, atrial fibrillation, and cancer onsets [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%